Politik Uang dan Perubahan Pandangan Politik di Kecamatan Pagelaran Pasca Runtuhnya Orde Baru - Lhotse Sumarno; Nanda Harda Meiji; Deny Wahyu Apriyadi (Mahesa Research Center, 2022)
Nowdays As the world of politics continues to be uncertain as a result of the political struggle of money. So it is in the district district where this area becomes the county's most unfortunate election. Political parties scramble for votes through the politics of money. Moreover, some of them managed to make it to the legislative candidate list in the 2019 elections. The study USES qualitative methods with a descriptive qualitative approach with observation and interviews to inform and analyze the involvement of the citizen in politics. It comes down to a change in politics caused by money. Using an impressive sampling model, the selection of informants in this research was more important to caleg's changing party in his politics. But there seems to be various tricks to get people to vote. There are still pragmatic ways of using both goods and services to smooth the road into a caleg. This led to a different use of money in the sense of buying out citizens' votes. However, the politics of money is accepted because of the notion that it is not good to refuse money. People have known from the beginning the motives and goals of the candidate. But on the other hand, society has its own set of candidates without force from the politics of money.